The Real Role of Management Accounting in Company Sustainability amidst Conditions of Uncertainty - CUACA, BENNY; WONGSOWINOTO, FRIDAYANI (Politeknik Negeri Bengkalis, 2024)
Business sustainability in a company faced with a situation of uncertainty can be influenced by internal factors and external factors of the company which can influence the company's current and future performance. Therefore, a real role is needed for management accounting which has the function of assisting management in planning, controlling and making decisions as an effort to minimize business risks. This research uses qualitative research with data collection techniques through literature study which is analyzed qualitatively. The results of his research concluded, first, that the role of management accounting in general helps company management in making strategic planning and budgeting, controlling costs, the resulting information can be used as a performance evaluation guide for further improvement and development, helping analyze data in making decisions that can minimize risk. business, and management accounting play a role in helping evaluate viable future company investment projects. Second, the real role of management accounting in company sustainability in the midst of conditions of uncertainty is the implementation of a management accounting information system in companies that fulfills the elements of breadth, timeliness, aggregation and integration.